Lateral-Torsional Buckling of a Bidirectional Exponentially Graded Thin-Walled C-Shaped Beam - Rezaiee-Pajand, M.; Masoodi, A. R.; Alepaighambar, A. (Mechanics of composite materials, 2022)
Based on the Euler–Bernoulli beam theory, an analytical closed-form solution to the lateral-torsional buckling moment of a bidirectional exponentially functionally graded monosymmetric C-shaped beam is proposed. The Young’s and shear moduli of the beam vary along its height and length direction. An exponential function is used to describe the variation in material properties along both the directions. For calculating the effective material properties along these directions, the rule of mixture is employed. Moreover, the effect of distributed lateral bracing is considered in the solution presented. Several numerical examples are solved to illustrate the high accuracy and performance of the solution.